Modeling and development of predictive controller for positioning control of electro-hydraulic actuator (EHA) system - Sulaiman, Siti Fatimah; Ngateni, Nurul Aini; Osman, Khairuddin; Samsudin, Sharatul Izah; Sulaiman, Noor Asyikin; Sunar, Noorhazirah (Wydawnictwo SIGMA-NOT, 2024)
An Electro-Hydraulic Actuator (EHA) is a hydraulic system that is commonly used in applications that require high power concentrations, efficient energy dissipation, or exceptionally high forces. The crucial part of this system is to control the position of its cylinder stroke at the desired position. Failure to properly control the position will cause the cylinder stroke position to be inaccurate. This study is proposed for this reason. The scope of this study consists of modeling and controlling the EHA positioning system. In this study, the system identification technique is used to model the EHA system, while predictive controller specifically Predictive Functional Controller (PFC) is proposed as a new strategy to control the position of the EHA system. Both modeling and controlling processes in this study fully utilise MATLAB software. To evaluate the effectiveness of the proposed PFC, the positioning performance of the PFC was compared with the basic controller (Proportional-Integral-Derivative (PID)) in terms of transient response performance. Comparison between the proposed PFC and the classical PID controller based on MATLAB Simulink showed that PFC can be used to control the EHA positioning system, however, the speed response of the system can be improved through certain modifications in the PFC algorithm.